The Influence of Motivation and Work Discipline on Employee Performance at Yamaha Arista Jatiwangi - Ade Sobariah Hasanah; Eli Dahlia; Salman Faisal (Journal of Applied Digital Business Management, 2024)
In a company there are many factors that affect employee performance, including seen from the motivation and discipline possessed by employees. This study aims to determine the effect of motivation and discipline on employee performance. This study uses descriptive and verification methods. Data collection techniques by distributing questionnaires. The population in this study were 35 employees, and used a saturated sampling technique of 35 people. This study uses a Likert measurement scale. Data analysis using normality tests, multiple regression analysis, multiple correlations, coefficients of determination and hypothesis testing using partial tests with t tests and simultaneous tests with F tests. The results of the study partially state that motivation has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. The results of the study simultaneously state that motivation and work discipline have a positive and significant effect together on employee performance.